Simultaneously Promoting Proton Conductivity and Mechanical Stability of SPEEK Membrane by Incorporating Porous g–C3N4 - Xiaoyao Wang; Benbing Shi (Membranes, 2025)
Proton exchange membranes are widely used in environmentally friendly applications such as fuel cells and electrochemical hydrogen compression. In these applications, an ideal proton exchange membrane should have both excellent proton conductivity and mechanical strength. Polymer proton exchange membranes, such as sulfonated poly(ether ether ketone) (SPEEK) membranes with high ion exchange capacity, can lead to higher proton conductivity. However, the ionic groups may reduce the interaction between polymer segments, lower the membrane’s mechanical strength, and even cause it to dissolve in water as the temperature exceeds 55 °C. The porous graphitic C3N4 (Pg–C3N4) nanosheet is an important two–dimensional polymeric carbon–based material and has a high content of –NH2 and –NH– groups, which can interact with the sulfonic acid groups in the sulfonated SPEEK polymer, form a more continuous proton transfer channel, and inhibit the movement of the polymer segment, leading to higher proton conductivity and mechanical strength. In this study, we found that a SPEEK membrane containing 3% Pg–C3N4 nanosheets achieves the optimized proton conductivity of 138 mS/cm (80 °C and 100% RH) and a mechanical strength of 74.1 MPa, improving both proton conductivity and mechanical strength by over 50% compared to the SPEEK membrane.